Progress of hydrogen subsonic commercial aircraft - Boretti, Alberto (Frontiers in Energy Research, 2023)
Hydrogen may substitute traditional hydrocarbon fuels in propeller and jet aircraft. In the case of propeller propulsion, the use of combustion engines is preferable to fuel cells plus electric motors. The conversion efficiency from chemical to mechanical energy at the propeller is larger with fuel cells, but the propulsion system is also larger, in addition to heavier. Fuel cells have a better appeal for novel urban air mobility solutions. Hybridization of gas turbine engines is beneficial for propeller and jet propulsion. The hydrogen aircraft architecture is strongly modified to accept much larger fuel tanks, having hydrogen a larger mass-specific-energy, but a smaller volume-specific-energy, than jet fuels, stored onboard liquid or cold-cryo/compressed. Conformal tanks may reduce the total aircraft volume vs. spherical/cylindrical tanks, the same as the use of novel composite structures to improve strength and reduce the weight of tanks. With conventional designs, the maximum-take-off weight slightly reduces, but the operating-weight-empty largely increases with hydrogen, for an 8%–15% larger energy consumption per pax and nm compared to hydrocarbon fuels. Fuel cell propeller propulsion also suffers from the weight of batteries and fuel cell stack. Non-conventional designs such as Blended-Wing-Body and hybridization may help reduce energy consumption. Renewable-hydrogen-only aircraft necessitate further development of aircraft technology before full deployment by 2035, providing renewable hydrogen will be cheap and abundant at the time, and the airport infrastructure developed. The introduction of hypersonic renewable-hydrogen-only aircraft could also be possible, given the progress in hypersonic technologies and the synergy with subsonic commercial aviation.